PEMILIHAN MODA TRANSPORTASI SETELAH ADANYA KERETA COMUTER LINE (STUDI DAERAH PENYANGGA JAKARTA) - Aris Munandar (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2015)
ABSTRACT This study aimed to get a general idea about the selection of transportation modes resident in the buffer after the comuter line. The research time of the month from May to July 2014. The population in this study were all passengers in the Depok , Bekasi , Tangerang stasiun . The sampling technique was done by purposive sampling, passengers who choose rail transportation mode before applying commuterline using other modes . Each station 30 so that the total of 90 respondents. Characteristic of the youngest respondents aged 16 years and the oldest 50 years with an average of 26.9 years . The Based work on non-civil . Based on the level of respondents at most high school education. Based on user characteristics of respondents have either two-wheel motor vehicles and driving licence (SIM) equipped . Motor vehicles used by the respondent as a feeder . Average of the marital status of unmarried respondents . For those who are married earned income respondents said inadequate needs . Inadequate income would find it difficult to save . Respondents largely did not participate in the community commuter line . Based on the characteristics of the movement of the majority of respondents travel destinations for work purposes . Based on the characteristics mode facility, respondents to travel departing in the morning , come home in the afternoon rush hour . Respondents went on a trip with other existing modes . Respondents do not make the shift from the other trains . Travel time required respondents to make every trip is in accordance with her wishes . For short trips ( 10 stasion ) takes 50 minutes . Resonden not rest / sleep when the train . The cost for short trips ( 10 stations ) of Rp 3,000 , including low cost . Respondents were more likely to use multi- trip cards than single trip. The respondents were unable to seat. Keywords : comuter line , election , mode , transportation